2018
DOI: 10.1088/1367-2630/aabe3b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient optical pumping using hyperfine levels in 145Nd3+:Y2SiO5 and its application to optical storage

Abstract: Efficient optical pumping is an important tool for state initialization in quantum technologies, such as optical quantum memories. In crystals doped with Kramers rare-earth ions, such as erbium and neodymium, efficient optical pumping is challenging due to the relatively short population lifetimes of the electronic Zeeman levels, of the order of 100 ms at around 4 K. In this article we show that optical pumping of the hyperfine levels in isotopically enriched 145 Nd + 3 :Y 2 SiO 5 crystals is more efficient, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The long hyperfine lifetime compared to the optical lifetime means the 167 Er 3+ background can theoretically be reduced to < 0.01 dB, and the I = 0 isotope impurities will then dominate, leading to a predicted efficiency of 34.5%. This is similar to AFC delay line efficiencies demonstrated in Pr (35%) [15], Eu (32%) [16], and 145 Nd (33%) [17].…”
supporting
confidence: 83%
“…The long hyperfine lifetime compared to the optical lifetime means the 167 Er 3+ background can theoretically be reduced to < 0.01 dB, and the I = 0 isotope impurities will then dominate, leading to a predicted efficiency of 34.5%. This is similar to AFC delay line efficiencies demonstrated in Pr (35%) [15], Eu (32%) [16], and 145 Nd (33%) [17].…”
supporting
confidence: 83%
“…Interest in designing high-performance nonlinear optical (NLO) materials is growing rapidly due to their widespread applications in optical computing, optical communication, , optical switching, , optical logic functions, , dynamic image processing, , and many other optoelectronic fields. Recently, a unique class of compounds known as electrides having isolated excess electrons has garnered great interest from the chemical society. Due to this nontrivial electronic structure, they are easily polarizable and can serve as superior nonlinear optical materials. ,, Electrides due to their certain interesting properties such as the ultralow work function, relatively high catalytic activity, high electronic mobility, and optical and anisotropic properties have great potential for various applications. In 1983, Dye and co-workers fabricated the first organic crystalline electride consisting of organic complexant cages in which alkali metals and electrons were trapped . Since then, various organic and inorganic electrides have been reported in literature, and their novel electronic structures have been investigated both computationally and experimentally. …”
Section: Introductionmentioning
confidence: 99%
“…As an example, we estimated the magnetic fields, SLR, and flip-flop rates necessary to achieve DEOP as efficiently as in 171 Yb 3þ ∶Y 2 SiO 5 for Er 3þ and Nd 3þ ions in Y 2 SiO 5 (see Table S III in Supplemental Material [38]). These materials have been investigated for quantum memories, optical to microwave quantum transducers, and quantum processors [2,30,[52][53][54]. We first found that magnetic fields in the range 1-100 mT are sufficient to partially remove transition overlap, thanks to Γ inh ¼ 0.2 (6) GHz and g ¼ 15 4for Er 3þ (Nd 3þ ).…”
Section: Discussionmentioning
confidence: 99%